Diurnal variations in tissue factor and tissue factor pathway inhibitor concentrations in relation to on-treatment platelet reactivity: an analysis of patients with acute myocardial infarction. (2nd October 2020) - Boinska, Joanna; Koziński, Marek; Kasprzak, Michał; Ziołkowska, Katarzyna; Dziembowska, Inga; Ziołkowski, Michał; Kubica, Jacek; Rość, Danuta
Abstract: The aim of the study was to evaluate diurnal changes of tissue factor (TF) and tissue factor pathway inhibitor (TFPI) concentrations in relation to on-treatment platelet reactivity. The study group included 51 patients with acute myocardial infarction (AMI) treated with primary percutaneous coronary intervention and dual antiplatelet therapy. TF and TFPI concentrations were assessed using enzyme-linked immunosorbent assay kits. We found a significant increase of TF concentration in clopidogrel-resistant, but not clopidogrel-sensitive, patients at 10.00 a.m. (410.66 pg/mL) in comparison with 6.00 a.m. (250.99 pg/mL), 14.00 p.m. (255.12 pg/mL) and 19.00 p.m. (267.58 pg/mL). Moreover, TF concentration at 10.00 a.m. was 30% higher in clopidogrel-resistant than clopidogrel-sensitive patients ( p = .043). We failed to demonstrate diurnal variation in TFPI concentration in clopidogrel-resistant patients. However, TFPI concentration in clopidogrel-sensitive patients was significantly higher at 10.00 a.m. as compared with other sampling points ( p < .05). We observed a marked elevation in TF concentration at 10.00 a.m. only in aspirin-resistant patients and a significant increase in TFPI concentration at 10 a.m. only in aspirin-sensitive patients. Our findings suggest the presence of diurnal variations in TF and TFPI concentrations in AMI patients, with the highest thrombotic risk in patients with high on-treatment platelet reactivity in the midmorning.